Program komputerowy jako przedmiot umowy o dzieło - Żok, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Software development contract sensu stricto is often qualified as a contract for work. The aim of the article is to consider the relation between a bespoke computer program and work. In the conclusion of the conducted analysis it should be stated that it will not always constitute work in the sense of Art. 627 of the Civil Code. The lack of a precise description of bespoke software and the uncertainty of its realisation is an argument for the exclusion of immaterial goods from the scope of the contract for work. This last remark concerns particularly complicated computer programs, which are ordered most frequently and which are often under the copyright protection. However, simple computer programs will normally constitute the object of the contract for work.
Keywords: program komputerowy; umowa na rozwój oprogramowania; umowa o dzieła